Pengaruh Edukasi Media Booklet Terhadap Pengetahuan Pasien Diabetes Melitus Tipe 2 Peserta Prolanis Di Puskesmas Lima Kaum I Kabupaten Tanah Datar. - Rani, Jihan Shasika; Sari , Yelly Oktavia; Wahyuni, Fatma Sri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion or function. The prevalence of T2DM is increasing globally, including in Indonesia. However, patients’ knowledge regarding disease management remains relatively low. Continuous education is considered an essential strategy to improve disease control. Objective: This study aimed to analyze the effect of education using booklet media on improving knowledge among T2DM patients enrolled in the Chronic Disease Management Program (Prolanis) at Lima Kaum I Public Health Center, Tanah Datar Regency. Methods: The study employed a pretest-posttest control group design involving a total of 48 respondents, divided into an intervention group (received the booklet) and a control group. The research instrument used was the SDKS INA 1 questionnaire to assess patients’ knowledge. Data were analyzed using the Chi-Square test and the Wilcoxon test. Results: showed a significant increase in patients' knowledge after the educational intervention using the booklet (p=0.000; p<0.05). Conclusion: Therefore, booklet media is proven to be an effective educational tool for enhancing knowledge among patients with Type 2 Diabetes Mellitus.